Alpha-fetoprotein concentrations measured by radioimmunoassay in diagnosing and excluding hepatocellular carcinoma. Issue 6138 (2nd September 1978) - Johnson, P J; Portmann, B; Williams, R
Abstract : Serum alpha-fetoprotein (AFP) concentrations were estimated by sensitive radioimmunoassay in 30 patients with cirrhosis complicated by hepatocellular carcinoma and in 100 patients with cirrhosis in whom malignancy was excluded. Twenty-nine of the 30 patients with hepatocellular carcinoma had concentrations above 10 IU/ml (10.5 ng/ml) (median 3500 IU/ml (3675 ng/ml)), whereas only one of the 100 patients with cirrhosis and no tumour development had a raised concentration. Eleven out of 20 patients in whom hepatocellular carcinoma had developed in an apparently normal liver had raised AFP concentrations. In this group the differential diagnosis is usually secondary carcinoma, and three of 50 such patients had AFP concentrations above 10 IU/ml. Noting raised AFP concentrations is thus of considerable value both in detecting and in excluding hepatocellular carcinoma in cirrhosis, for in this case such concentrations gave only 1% false-positive and 3% false-negative results. They are less useful, however, in distinguishing between primary tumours arising in patients without cirrhosis and secondary hepatic deposits, giving 6% false-positive and 45% false-negative results.